On Euler’s lemma - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2023)
Some new versions of the proof of Euler’s lemma are considered. These allow to construct elementary proofs of Fermat’s theorem in the case n = 3.
Keywords: Fermat’s theorem; Euler’s lemma; diophantine equations; elemntary proof